Arginine-Based Inhibitors of Nitric Oxide Synthase: Therapeutic Potential and Challenges - Jan Víteček; Antonín Lojek; Giuseppe Valacchi; Lukáš Kubala (Mediators of Inflammation)
In the past three decades, nitric oxide has been well established as an important bioactive molecule implicated in regulation of cardiovascular, nervous, and immune systems. Therefore, it is not surprising that much effort has been made to find specific inhibitors of nitric oxide synthases (NOS), the enzymes responsible for production of nitric oxide. Among the many NOS inhibitors developed to date, inhibitors based on derivatives and analogues of arginine are of special interest, as this category includes a relatively high number of compounds with good potential for experimental as well as clinical application. Though this group of inhibitors covers early nonspecific compounds, modern drug design strategies such as biochemical screening and computer-aided drug design have provided NOS-isoform-specific inhibitors. With an emphasis on major advances in this field, a comprehensive list of inhibitors based on their structural characteristics is discussed in this paper. We provide a summary of their biochemical properties as well as their observed effects both in vitro and in vivo. Furthermore, we focus in particular on their pharmacology and use in recent clinical studies. The potential of newly designed specific NOS inhibitors developed by means of modern drug development strategies is highlighted.